2023
DOI: 10.3390/s23031712
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Virtual Reality in Post-Stroke Rehabilitation: A Systematic Review

Abstract: In recent years, next to conventional rehabilitation’s techniques, new technologies have been applied in stroke rehabilitation. In this context, fully immersive virtual reality (FIVR) has showed interesting results thanks to the level of immersion of the subject in the illusional world, with the feeling of being a real part of the virtual environment. This study aims to investigate the efficacy of FIVR in stroke rehabilitation. PubMed, Web of Science and Scopus were screened up to November 2022 to identify eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 97 publications
1
28
0
Order By: Relevance
“…The choice of environment used in this study was made in reference to previous studies. Previous studies have indicated that FIVR environments outperform SIVR and NIVR environments (Choi et al 2020b;Demeco et al 2023). Additionally, scientific publications have demonstrated the positive impact of embodiment (Matamala-Gomez et al 2022;Ventura et al 2023).…”
Section: Discussionmentioning
confidence: 97%
“…The choice of environment used in this study was made in reference to previous studies. Previous studies have indicated that FIVR environments outperform SIVR and NIVR environments (Choi et al 2020b;Demeco et al 2023). Additionally, scientific publications have demonstrated the positive impact of embodiment (Matamala-Gomez et al 2022;Ventura et al 2023).…”
Section: Discussionmentioning
confidence: 97%
“…[28][29][30] A scoping review also discovered, in contrast to another one, that many studies included psychological outcomes, including immediate intrinsic motivation, anxiety, depression, and mood. [28,[31][32][33] ADL and balance analysis indicated that improvement in BBS (4.78%) was significantly different between the DRA and CPT groups. This finding was in concordance with a previous study by Sana et al (2023) who reported increased improvement in balance (11.1%) following 8 weeks of virtual reality therapy than vestibular rehabilitation therapy in 34 patients with subacute hemiplegic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In post-stroke rehabilitation, common inclusion criteria may involve factors such as a certain time since the stroke event, specific types of strokes, and a particular level of upper limb motor impairment. On the other hand, exclusion criteria may consider factors such as severe cognitive impairments or co-morbidities that could interfere with the study intervention [26]. By carefully selecting participants based on the following inclusion and exclusion criteria, the study aimed to create a more homogeneous sample.…”
Section: Participantsmentioning
confidence: 99%